The Concept of Shariah Compliant Hotel Business in Malaysia - Hashim, Nur Iman; Mohd Fauzi, Nadzirah (Online Journal of Research in Islamic Studies, 2019)
This paper concerned with the concept of Shariah Compliant Hotel (SCH) business which nowadays are widely promoted by Malaysian government to cater the growing of Muslim travelers market. Based from the observation, it can be said that the uniform concept of SCH in Malaysia is still not exist to guide the operation of SCH businesses in Malaysia. Moreover, the suggestion from several past researchers regarding the formation of the standardized concept of SCH business to guide those parties who involved in SCH business in Malaysia make this topic relevant to be discussed further. Therefore, several past research related to the topic of SCH business was reviewed in order to find out the major attributes and requirements to becoming the real SCH business. Hopefully, the information provided by this paper will able to assist in the next action towards formatting the concept of SCH business in Malaysia.